A theoretical model of the human eye based on ultrasound and corneal data - Falhar, Martin; Rehak, Jiri (Oficyna Wydawnicza Politechniki Wrocławskiej, 2009)
The purpose of this study was to create a theoretical model of the eye based on a comparison of the real spherical equivalent of the eye and the calculated value of the axial refraction. The main contribution of this model is that it enables calculation of the equatorial plane of the lens for accurate assessment of the IOL position for a spherical eye model. The Gullstrand model of the eye was used as the source eye model and this was modified for the purposes of this study. The axial refraction of the final model of the eye was compared with the spherical equivalent. The accuracy of the developed model was statistically confirmed using statistic tests. Individual calculation of the axial refraction using it shows that IOL calculation is possible without any general statistical presumptions. It permits the calculation of variables with an accuracy accepted by inferential statistics. The accuracy of this theoretical eye model however, is limited by extreme values of variables – an extreme value provides a less accurate result.
Optica Applicata, Vol. 39, 2009, nr 1, s. 195-210
Keywords: optyka; biometry; theoretical eye model; lens; nucleus; intraocular lens (IOL); intraocular lens formula; axial refraction